2015
DOI: 10.2147/tcrm.s68010
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban for the prophylaxis and treatment of deep vein thrombosis and pulmonary embolism: an evidence-based review

Abstract: Venous thromboembolism (VTE) results in significant morbidity and mortality. The prevention and treatment of VTE is managed with anticoagulant therapy, historically parenteral anticoagulants such as unfractionated heparin, low molecular weight heparin, and fondaparinux, and oral vitamin K antagonists such as warfarin. In the last few years, several target-specific oral anticoagulants have been developed, including the direct thrombin inhibitor dabigatran and anti-Xa inhibitors rivaroxaban, apixaban, and edoxab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The study found modest increase in apixaban exposure off hemodialysis and the limited removal of apixaban during hemodialysis in ESRD patients, suggesting the medication can be used without dose modification. FDA, therefore, recommends using the dose of 5 mg twice a day for nonvalvular AF and 2.5 mg twice a day for prevention of thromboembolic recurrence in venous thromboembolism (VTE) . At present, the clinical data are only limited to observational studies included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The study found modest increase in apixaban exposure off hemodialysis and the limited removal of apixaban during hemodialysis in ESRD patients, suggesting the medication can be used without dose modification. FDA, therefore, recommends using the dose of 5 mg twice a day for nonvalvular AF and 2.5 mg twice a day for prevention of thromboembolic recurrence in venous thromboembolism (VTE) . At present, the clinical data are only limited to observational studies included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Apixaban inhibits factor X that is an essential clotting factor in both the intrinsic and extrinsic coagulation pathways. In addition, it inhibits prothrombinase (an enzyme that catalyses conversion of prothrombin to thrombin) and platelet aggregation both of which are essential components in clot development 10. It is also suggested that the decreased thrombin level associated with inhibition of factor X may modify whole blood clot structure to a more penetrable organisation 11.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Substitution of heparin is the main therapy in inpatient prophylaxis of thrombosis and new oral anticoagulants need to show efficacy. 13 Nevertheless, thrombotic events are common and major complications in free flap reconstruction of the lower extremity and can lead to flap failure. Fujiki et al observed that venous thromboses are more frequent than arterial thromboses in free flaps to the lower extremities.…”
Section: Discussionmentioning
confidence: 99%